Crohn’s Disease Complicated by Rare Types of Intestinal Obstruction: Two Case Reports - Xia, Kai; Gao, Renyuan; Wu, Xiaocai; Ruan, Yu; Wan, Jian; Wu, Tianqi; Wang, Fangtao; Lin, Yin; Yin, Lu; Chen, Chunqiu (Frontiers in Medicine, 2022)
Intestinal obstruction is one of the most common complications of Crohn's disease (CD), jeopardizing the quality of life of patients. Numerous factors may contribute to intestinal obstruction in CD. Thus far, the primary reason has been identified as intestinal fibrosis caused by repeated chronic inflammation during the active phase of CD. Herein, we report two rare complicated CD cases and provide a reference for the clinical diagnosis and treatment of similar patients. Case one involves capsule endoscope retention in the small intestine of one CD patient concurrent with intestinal obstruction. Case two is a CD patient with intestinal obstruction caused by a mesangial hernia and ileal stenosis. Individualized and minimally invasive surgical intervention ultimately resulted in the successful management of these two patients. The two cases serve as an excellent guide for diagnosing and treating CD patients who present with similar symptoms.